2014
DOI: 10.1021/ja413179n
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxygen Activation by Carbanion Intermediates of Nitrogen-Doped Graphitic Carbon

Abstract: Nitrogen-doped graphitic carbon has been intensively studied for potential use as an electrocatalyst in fuel cells for the oxygen reduction reaction (ORR). However, the lack of a mechanistic understanding on the carbon catalysis has severely hindered the progress of the catalyst development. Herein we use a well-defined graphene nanostructure as a model system and, for the first time, reveal an oxygen activation mechanism that involves carbanion intermediates in these materials. Our work shows that the overpot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 39 publications
6
68
1
Order By: Relevance
“…Therefore, the monodentate activation of molecular oxygen on optimal nitrogen-doped graphitic materials would be enabled by hydrogenation and driven by the available charge. The identified activation mechanism should take place in the same potential region where the hydrogenation process takes place, as has been already observed experimentally [32]. By focusing on the monodentate activation, fundamental effects would have been brought to light, explaining the experimental observations originating this research, and enabling the discussion of different configurations.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Therefore, the monodentate activation of molecular oxygen on optimal nitrogen-doped graphitic materials would be enabled by hydrogenation and driven by the available charge. The identified activation mechanism should take place in the same potential region where the hydrogenation process takes place, as has been already observed experimentally [32]. By focusing on the monodentate activation, fundamental effects would have been brought to light, explaining the experimental observations originating this research, and enabling the discussion of different configurations.…”
Section: Discussionsupporting
confidence: 57%
“…It has been suggested that the hydrogenation of pyridinic-nitrogen dopants in graphitic materials can be involved in the activation of the ORR in alkaline solutions [32]. Since this process depends not only on the pH but also on the electrode potential, the hydrogenation of pyridinic nitrogen-dopants can take place actually under alkaline conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The virtual invariance of the double layer indicates that the Aza-CMP material does not have any functional groups in the material capable of having a redox process, aside from those related to the peaks at 0.16 V, which assures the quality of the material. This latter peaks can be associated to the hydrogenation of the nitrogen atoms, as has been proposed for nitrogendoped graphene 32 When the Aza-CMP material is modified with Co(II), the double layer increases, which clearly indicates that the cobalt has been clearly incorporated into the Aza-CMP materials (Figure 2). However, the peaks at 0.16 V disappear.…”
Section: Resultsmentioning
confidence: 56%
“…Similar pH-dependent redox activity was reported in a nitrogen-doped graphitic carbon ORR catalyst. 9 With the discussed experimental and computational data in hand, the following mechanism for the 2e − reduction of O 2 on Ni 3 (HITP) 2 emerges (Scheme 1):…”
Section: Acs Catalysismentioning
confidence: 99%